National conference on skills and competencies in education 2005. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2005)
The development of graduates’ workplace skills and competencies is the responsibility of educational institutions, industry as well as the graduates themselves. This was one of the messages conveyed to the participants of the recently held National Conference on Skills and Competencies in Education 2005.